A Band Rejection Filter of High Current Radio Frequency Ion Source for Neutral Beam Injector. (4th July 2021) - Liu, Wei; Cui, Qinglong; Liu, Sheng; Liang, Lizhen; Zhao, Yuanzhe; Song, Shihua
Abstract: As a promising ion source, the radio frequency (RF)–driven ion source is widely equipped in the neutral beam injector of magnetic-confinement fusion devices. In order to study the characteristics of the RF-driven ion source and plasma generation, a prototype RF negative ion source–based test facility has been developed at the Institute of Plasma Physics, Chinese Academy of Sciences. Many diagnostic tools have been developed for this test facility. The electrostatic sensors are a critical part of the diagnostic methods. Considering the electrostatic sensors to be used in the harsh RF environment, an improved RF compensation circuit [band rejection filter (BRF)] has been developed that effectively reduces RF interference and improves signal acquisition accuracy. The BRF has been successfully verified for frequency response characteristics in a magnitude plot.